2008
DOI: 10.1345/aph.1l204
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Reporting and Scientific Quality of Meta-Analyses of Randomized Controlled Trials of Treatments for Anxiety Disorders

Abstract: Reporting/scientific quality was considered less than fair-to-good. Stakeholders should strive for higher scientific quality of meta-analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…These results are also similar to those reported by Bereza and colleagues [31] in the only other review of meta-analyses of anxiety disorder RCTs. This is in spite of methodologic differences between the reviews, such as the inclusion of pooled analyses and pediatric meta-analyses by Bereza et al [31] and their failure to include any Cochrane reviews in their analysis. The results of this review accordingly support the sentiment of other authors that there is scope for improving both the conduct of meta-analyses and the way in which they are reported.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are also similar to those reported by Bereza and colleagues [31] in the only other review of meta-analyses of anxiety disorder RCTs. This is in spite of methodologic differences between the reviews, such as the inclusion of pooled analyses and pediatric meta-analyses by Bereza et al [31] and their failure to include any Cochrane reviews in their analysis. The results of this review accordingly support the sentiment of other authors that there is scope for improving both the conduct of meta-analyses and the way in which they are reported.…”
Section: Discussionsupporting
confidence: 92%
“…The overall scores of the treatment meta-analyses included in this review on the QUOROM and ISQRO are consistent with the range of results (QUOROM, 9-12.3; ISQRO, 2.7-4.7) reported by other studies of the quality of meta-analyses of RCTs in the health sciences [4,21,27,29,30]. These results are also similar to those reported by Bereza and colleagues [31] in the only other review of meta-analyses of anxiety disorder RCTs. This is in spite of methodologic differences between the reviews, such as the inclusion of pooled analyses and pediatric meta-analyses by Bereza et al [31] and their failure to include any Cochrane reviews in their analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Bereza et al56 and Junhua et al70 reported that there was a need to improve the quality of reporting of reviews, while Shea et al82 concluded that the quality of Cochrane musculoskeletal systematic reviews was good. Hemels et al68 used only the QUOROM checklist and they concluded that the quality of meta-analyses in studies on major depressive disorder was marginally acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…Dozens of systematic reviews have explored the extent of adherence to different reporting guidelines in some areas of health research. 5–9 Samaan et al 10 went one step further and performed a systematic review of systematic reviews assessing adherence to reporting guidelines. As they considered a broad range of clinical areas and study designs since the creation of the CONSORT Statement, their results provided a global picture of compliance with reporting guidelines in health research.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, several reviews have analysed the quality of reporting in different clinical areas and for different studies, 5–10 but no scoping review investigating what actions have been taken or suggested in order to improve compliance with reporting guidelines has been performed so far. Given the low levels of completeness of reporting in health research observed 10 and the need of taking further actions to mitigate this problem, we consider that performing such a scoping review is warranted.…”
Section: Introductionmentioning
confidence: 99%